ANALISIS KAUSALITAS ANTARA HUTANG LUAR NEGERI DENGAN DEFISIT ANGGARAN PENDAPATAN DAN BELANJA NEGARA INDONESIA TAHUN 1978 - 2003: PENDEKATAN ERROR CORRECTION MODEL (ECM) - Andiarma Tesamaris; Siti Fatimah Nurhayati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2005)
National development in Indonesia needs the big enough number of funds. Principally, there are two kinds of the fund sources, i.e. the domestic funds and foreign funds. In fact, the number of domestic funds is often far smaller than that is needed, so forcing to search for alternative fund sources, namely, foreign loan. Foreign loan risk is big enough. The inflow of foreign loan will increase money in circulation, so that it can trigger inflation. On the other hand, it is obligation to pay in installment of the principal loan and its interest, which annually always burdens the national budget so that it results in larger deficit. All make economic situation more difficult for the future. While from year to year, the fund need in a country is increasingly bigger. It is interesting to study how causality correlation pattern between foreign loan and budget deficit. The result of this research showed that there are two-way causality correlations, namely, foreign loan influences budget deficit and budget deficit influences foreign loan.